Spatial distributions of on- and off-responses determined with the multifocal ERG - Rodrigues, Anderson R.; Da Silva Filho, Manoel; Silveira, Luiz Carlos L.; Kremers, Jan (Documenta Ophthalmologica, 2010)
We studied the contribution of retinal on- and off-mechanisms in the multifocal electroretinogram (mfERG) by measuring responses to sawtooth stimuli. Six healthy subjects participated in this study. Rapid-on and rapid-off sawtooth stimuli with a period of 427 ms were presented in a multifocal pattern composed of 19 hexagons. The stimuli were interleaved with a blank field of the mean luminance and chromaticity. On- and off-responses were added to extract response asymmetries. The amplitudes of on-, off-, and added-responses were determined for different eccentricities relative to a signal baseline that was defined as the average of the electrical level recorded in two different time windows in which no responses were present. Measurements were repeated with eight different stimulus stretch factors to account for changes in retinal cell density as a function of eccentricity. The amplitudes of all ERG components decreased with increasing eccentricity for all stretch factors. For stretch factors between 0 and 20, responses to the central and immediately adjacent hexagons were large in amplitude. For more peripheral hexagons, the responses were very small or absent. Three components were identified in the on-responses (N20(on), P46(on) and N100(on)). In the off-responses, we found one positive (P20(off)) and one negative (N90(off)) component, whereas in the addition, three components (N20(add), P46(add) and N100(add)) could be observed. The N20(on) and P46(on) amplitudes decreased less steeply with eccentricity than the N100(on) amplitude, whilst the P20(off) and N90(off) amplitudes exhibited a similar decrease with eccentricity. In the addition, the two negative components exhibited a similar decrease in amplitude as a function of eccentricity and decreased more steeply than the positive component. The number of stimulated cones and retinal ganglion cells was estimated from anatomical data and compared with the responses. The spatial properties of the amplitudes of N20(on), P46(on), P20(off), and N90(off) and P46(add) were similar to those of the stimulated cone numbers. The remaining components had spatial characteristics that resembled those of the retinal ganglion cells. It is proposed that the ERG asymmetries revealed in the summed responses have post-receptoral origins, some of them reflecting the activity of the ganglion cell population. The use of sawtooth stimuli provide, similar to the pattern ERG, a way to record the ERG asymmetries.
Keywords: On- and off-mechanisms; Multifocal ERG; Retinal pathways; Retinal eccentricity